Marketing communication strategy using online platforms to build brand image at The Westin Resort Nusa Dua Bali - I Kadek Eri Suma Andika; Ni Luh Eka Armoni; I Gede Mudana; I Putu Krisna Arta Widana (International Journal of Green Tourism Research and Applications, 2021)
Purpose, in simple words tell readers about the aim of this research. Research methods, give name, brand, type of tools, methods, software, review, and survey that have been used to do this research. Results and discussion, write only main results and discussion in few words. A summary of your key findings. An explanation of why your findings and key message contribute to the field/s. No formula needed and avoid quotes and extensive references. (maximum 250 words). The purpose of this research is to determine the strengths, weaknesses, opportunities and threats of marketing communication in building brand image, to find out the marketing communication strategy that should be used by marketing communication departments in building brand image. Data collection methods used were observation, interviews, documentation and questionnaires. The analysis techniques used are qualitative descriptive analysis, quantitative descriptive analysis, Internal Factor Analysis Summary (IFAS) Matrix, External Factor Analysis Summary (EFAS) Matrix, Internal-External Matrix (IE), and SWOT Analysis. The results showed that there were internal and external factors that influence marketing communication conducted by the marketing communication department at The Westin Resort Nusa Dua, Bali. Based on the results of IFAS matrix analysis, the main strengths are good relations with all partners, the media, influencers, guests and also the community, while the main weaknesses are responding to complaints and providing solutions to trip advisor reviews, OTA reviews and also social media. Based on the results of the EFAS matrix analysis, it is known that the main opportunity is technological development while the minor threats faced are The Westin Resort Nusa Dua, Bali position in the competition and natural disasters such as volcanic eruptions, earthquakes, floods, etc. The results of the IE matrix research showed the company position in the Growth (Cell V). SWOT analysis produces 6 alternative marketing communication strategies that can be used in building brand image.